Grief as social experience: Death and bereavement in Lihir, Papua New Guinea - Hemer, Susan R. (The Australian journal of anthropology, 2010)
This paper explores the nature of grief in Lihir, Papua New Guinea, in light of psychological theories of bereavement and grief. Anthropologists have demonstrated that culture has an impact on both the expression and experience of grief and can offer both a challenge to established theories and new perspectives on the conceptualisations and experiences of the bereaved. Until recently, ‘grief work’ was the foremost model for understanding bereavement as a psychological process and was also used by anthropologists in cross-cultural work. However, since the 1990s, a number of alternative models of normal grief have emerged, including the dual process coping model and the model that proposes resilience as a central concept. These newer models, particularly the one which incorporates resilience, offer more for understanding grief in Lihir. The article argues that grief in Lihir has a phase of sorrow and worry that is dealt with through the sociality and activity of the mourning period, and then a longer phase of active remembering and forgetting of the deceased. The social and cultural context of bereavement is not adequately captured in current psychological conceptualisations of social support, which need to be broadened to encompass cross-cultural material.